SHARIA LOGISTICS: SHOULD IT BE IMPLEMENTED IN MODERN BUSINESS? - Arief Rachman (Journal of Islamic Studies [Z-ISLAMICA], 2025)
This study discusses the importance of implementing sharia logistics in modern business, seeing the times and the demands of the needs of Muslims, especially Indonesia as a big house for the world's Muslims. This research uses a descriptive qualitative method with secondary data sources accessed from journals, books, previous research results, and reliable websites that can be used as reference sources. The results of this study show that sharia logistics integrates Islamic sharia principles into the supply chain, ensuring halalness, hygiene, and fairness in the distribution of goods. The benefits include fulfillment of religious principles, improved quality of goods, and increased social justice. However, the challenges of additional costs and limited resources are also faced. With the right investment, sharia logistics can build consumer confidence, support economic growth, and promote religious values.